Continuous texture evolution during staged solid solution of Al‐Cu‐Mg and the influence on fatigue resistance. Issue 3 (23rd November 2020) - Shen, Fanghua; Li, Wenfang; Xie, Chunxiao; Zhou, Zirong; Chen, Juming; Yi, Danqing; Chen, Yuqiang; Jiang, Bo; Sun, Zhenzhong
Abstract: Continuous texture evolution of the Al‐Cu‐Mg alloy during the staged solid solution and corresponding influence on fatigue property has been studied by means of X‐ray diffraction, electron back scattered diffraction and scanning electron microscopy. The characteristic texture transition rate XCGB and orientation streamline approach was introduced to further investigate the behind mechanisms. The results show that the two‐step solid solution could significantly enhance the XCGB, thereby contributes to reduce the fatigue crack growth rate of Al‐Cu‐Mg T3 sheet during stage Π. The near Cube texture with high Schmid factor (SF) and low Taylor factor (TF) tends to induce significant crack deflection, crack closure and strengthened planar slip. The potential 60°<1, −1, 1> twin relation and mutual transformation existed between Goss and P texture would further reduce the fine random orientation grain and inter‐granular fatigue crack extension. Such above effects would be responsible for the excellent correspondence between XCGB and fatigue resistance.